Comparative analysis of Hox downstream genes in Drosophila - Hueber, Stefanie Diana; Lohmann, Ingrid (Development, 2007)
Skip to Next Section Functional diversification of body parts is dependent on the formation of specialized structures along the various body axes. In animals, region-specific morphogenesis along the anteroposterior axis is controlled by a group of conserved transcription factors encoded by the Hox genes. Although it has long been assumed that Hox proteins carry out their function by regulating distinct sets of downstream genes, only a small number of such genes have been found, with very few having direct roles in controlling cellular behavior. We have quantitatively identified hundreds of Hox downstream genes in Drosophila by microarray analysis, and validated many of them by in situ hybridizations on loss- and gain-of-function mutants. One important finding is that Hox proteins, despite their similar DNA-binding properties in vitro, have highly specific effects on the transcriptome in vivo, because expression of many downstream genes respond primarily to a single Hox protein. In addition, a large fraction of downstream genes encodes realizator functions, which directly affect morphogenetic processes, such as orientation and rate of cell divisions, cell-cell adhesion and communication, cell shape and migration, or cell death. Focusing on these realizators, we provide a framework for the morphogenesis of the maxillary segment. As the genomic organization of Hox genes and the interaction of Hox proteins with specific co-factors are conserved in vertebrates and invertebrates, and similar classes of downstream genes are regulated by Hox proteins across the metazoan phylogeny, our findings represent a first step toward a mechanistic understanding of morphological diversification within a species as well as between species.